2016
DOI: 10.4049/jimmunol.1501921
|View full text |Cite
|
Sign up to set email alerts
|

Effector γδ T Cell Differentiation Relies on Master but Not Auxiliary Th Cell Transcription Factors

Abstract: γδ T lymphocytes are programmed into distinct IFN-γ–producing CD27+ (γδ27+) and IL-17–producing CD27− (γδ27−) subsets that play key roles in protective or pathogenic immune responses. Although the signature cytokines are shared with their αβ Th1 (for γδ27+) and Th17 (for γδ27−) cell counterparts, we dissect in this study similarities and differences in the transcriptional requirements of murine effector γδ27+, γδ27−CCR6−, and γδ27−CCR6+ γδ T cell subsets and αβ T cells. We found they share dependence on the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 71 publications
(109 reference statements)
4
67
0
Order By: Relevance
“…Whether CCR6 repression in Th17 cells occurs to disrupt barrier tissue-homing and promote recruitment to inflamed tissue, as we show in γδT17 cells, is unclear. Despite γδT17 cell development occurring independently of IRF4 and BATF4950, we report that these factors suppress Ccr6 expression in γδT17 cells upon IL-23- and IL-1β-driven activation. This is likely to be cooperative, as has been shown during Th17 cell development43.…”
Section: Discussionmentioning
confidence: 56%
“…Whether CCR6 repression in Th17 cells occurs to disrupt barrier tissue-homing and promote recruitment to inflamed tissue, as we show in γδT17 cells, is unclear. Despite γδT17 cell development occurring independently of IRF4 and BATF4950, we report that these factors suppress Ccr6 expression in γδT17 cells upon IL-23- and IL-1β-driven activation. This is likely to be cooperative, as has been shown during Th17 cell development43.…”
Section: Discussionmentioning
confidence: 56%
“…Because the transcriptional profiles of Th17 cells and gdT17 cells are similar in many aspects (28,29), we investigated whether IL-2 was a relevant determinant of thymic gdT17 development. Thymic IL-2 expression decreases before birth and resumes postnatally (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…None of the auxilliary transcription factors of the Th17 profile, which have recently been described to be dispensable for the development of gdT17 cells (29), were regulated (Fig. 7A).…”
Section: Engagement Of the Gd Tcr Contributes To The Commitment Of Gdmentioning
confidence: 91%
“…A previous report suggested that T-bet and RORγt promote the differentiation of T cells into Th1/Tc1 and Th17/Tc17 subsets, respectively [47]. Recently, it has become clear that both Th1 and Th17 cytokines are key players in the development of RA [48]. Furthermore, we observed that Sema7A significantly enhanced the production of Th17/Tc17 cytokines, including IFN-γ, IL-22, and IL-17, in comparison with cells treated with DSema7A.…”
Section: Discussionmentioning
confidence: 99%